Electrophysiologic Study and Ablation in Nepal - Our Initial Experience - Rajbhandari, Sujeeb; KC, Man Bahadur; Sharma, D; Shrestha, MP; Niak, Ajaya (Nepalese Heart Journal, 2004)
Cardiac electrophysiology study (EPS) is one of the most advanced, challenging and a complex branch of invasive cardiology. It involves placement of large sized multipolar catheters in various chambers of the heart. They are used to map and also to ablate the culprit focus of arrhythmia generation. Supraventricular arrhythmias are a nuisance as the pharmacological treatment is only suppressive. When done by experts, the procedure can be curative. During the month of October 03, twelve cases were selected for EPS.